Celestial navigation in the GPS age - Karl, John H. (Paradise Cay Publications, Inc. Celestaire,Inc., 2007)
Celestial Navigation in the GPS Age by John Karl This revised and expanded edition of this popular CN book now introduces simple tabular sight reductions first, followed by calculator methods for those wishing to take full advantage of their flexibility. Of course it retains the same unprecedented clear and accurate explanation of CN mysteries, such as the role of the assumed position , and how positions and celestial LOPs can be plotted with no assumptions